The concept of the physical self and its relationship to social fears among female students at the College of Sports Sciences and Physical Activity at King Saud University - almedihesh , Atheer; Haggag , Mohamed (Journal of Physical Education, 2024)
The study aimed to identify the concept of the physical self and the level of social fears among female students of the College of Sports Sciences and Physical Activity, and the relationship between the physical self and social fears, and to find out the extent of the influence of the physical self and its connection to social fears on female students of the College of Sports Sciences and Physical Activity.The study used the descriptive approach, and the study sample consisted of female students from the College of Sports Sciences and Physical Activity at King Saud University. The sample included (425) female students, who were selected by a simple random method. The study tools included a physical self-esteem scale, a social fears scale, and a data inventory form for female students.The results showed that the level of physical self-concept among the study sample was high, and the level of the degree of social fears was moderate, and it became clear that there was a statistically significant inverse correlation between the total degree of physical self-concept and social fears and their dimensions. This indicates that the higher the level of physical self-concept among female students at the College of Science Sports and physical activity The level of social fears decreased, and it was found that there were no differences according to the demographic variables (specialization - level) for the two scales: physical self-concept and social fears.